2016
DOI: 10.1002/nbm.3608
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic DTI accurately identifies early glioma cell migration: correlation with multimodal imaging in a new glioma stem cell model

Abstract: Monitoring glioma cell infiltration in the brain is critical for diagnosis and therapy. Using a new glioma Glio6 mouse model derived from human stem cells we show how diffusion tensor imaging (DTI) may predict glioma cell migration/invasion. In vivo multiparametric MRI was performed at one, two and three months of Glio6 glioma growth (Glio6 (n = 6), sham (n = 3)). This longitudinal study reveals the existence of a time window to study glioma cell/migration/invasion selectively. Indeed, at two months only Glio6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
(46 reference statements)
3
21
0
Order By: Relevance
“…This becomes even more evident in the tractography results -where the decellularised vessels yield no helically arranged tracts ( Figure 5). This result highlights the significance of cellular content and corroborates findings in a previous ex vivo DTI study on cell migration in brain tumours 40 , where the authors saw a decrease in FA and increase in MD when cells migrated out of a region of interest.…”
Section: Discussionsupporting
confidence: 90%
“…This becomes even more evident in the tractography results -where the decellularised vessels yield no helically arranged tracts ( Figure 5). This result highlights the significance of cellular content and corroborates findings in a previous ex vivo DTI study on cell migration in brain tumours 40 , where the authors saw a decrease in FA and increase in MD when cells migrated out of a region of interest.…”
Section: Discussionsupporting
confidence: 90%
“…In mouse models, the very small brain volume is a real limitation to achieving high spatial resolution in a reasonable time-frame as the signal-to-noise ratio achievable for a single image voxel tends to be low. For the purposes of this study, DTI was performed ex vivo using exogenous gadolinium-based MRI contrast agents 30 , 31 to reduce the relaxation times, in particular the longitudinal value T 1 . In these conditions, acquisition time was accelerated, and a high isotropic spatial resolution (80 µm) was attained with a signal-to-noise ratio of 104.…”
Section: Discussionmentioning
confidence: 99%
“…After removing surrounding skin and muscles, the skulls containing intact brains were immersed in the fixing solution for four days, and then transferred to a Fomblin (FenS chemicals) bath for at least eleven days after brain fixation. This schedule provided homogeneous distribution of the Gd-DOTA throughout the whole brain 31 .…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the specific anatomical location of the frontal lobe, the relationship between motor cortex gliomas and the surrounding fiber bundles is more complicated than for other intracranial tumors. Previous investigations 13 15 focused on the qualitative analysis of fiber bundles that may be involved in motor cortex tumors using traditional imaging data. These studies were only able to assess changes in the surrounding fibers due to invasion or edema.…”
Section: Discussionmentioning
confidence: 99%
“…A DTI glioma study revealed significant glioma-related changes in many white matter regions, including changes in the degree of anisotropy, average diffusion coefficient (AD), and other DTI coefficients; however, no conventional MRI study has reported glioma-related signal changes 11,12 . These changes identified by DTI may indicate the invasion and spread of early tumor cell precursors that may not be detected with conventional MRI 13 . However, previous studies have typically focused on the analysis of FA dispersion values and related issues of one or more white matter fiber pathways, but overall have lacked voxel-level assessments.…”
mentioning
confidence: 99%